Discovery and Recommendation Systems for Scientific Data - Xue, Zhaokun. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Computer Science.; Advisor: Alva Couch.; Committee: Liping Liu, Michael Hughes, Mark Hempstead, Tingjian Ge, David Tarboton, and Anselm Blumer.; Keyword: Computer science.